Effect of empagliflozin on circulating proteomics in heart failure: mechanistic insights into the EMPEROR programme. (26th August 2022) - Zannad, Faiez; Ferreira, João Pedro; Butler, Javed; Filippatos, Gerasimos; Januzzi, James L; Sumin, Mikhail; Zwick, Matthias; Saadati, Maral; Pocock, Stuart J; Sattar, Naveed; Anker, Stefan D; Packer, Milton
Abstract: Aims: Sodium-glucose co-transporter 2 (SGLT2) inhibitors improve cardiovascular outcomes in diverse patient populations, but their mechanism of action requires further study. The aim is to explore the effect of empagliflozin on the circulating levels of intracellular proteins in patients with heart failure, using large-scale proteomics. Methods and results: Over 1250 circulating proteins were measured at baseline, Week 12, and Week 52 in 1134 patients from EMPEROR-Reduced and EMPEROR-Preserved, using the Olink® Explore 1536 platform. Statistical and bioinformatical analyses identified differentially expressed proteins (empagliflozin vs. placebo), which were then linked to demonstrated biological actions in the heart and kidneys. At Week 12, 32 of 1283 proteins fulfilled our threshold for being differentially expressed, i.e. their levels were changed by ≥10% with a false discovery rate <1% (empagliflozin vs. placebo). Among these, nine proteins demonstrated the largest treatment effect of empagliflozin: insulin-like growth factor-binding protein 1, transferrin receptor protein 1, carbonic anhydrase 2, erythropoietin, protein-glutamine gamma-glutamyltransferase 2, thymosin beta-10, U-type mitochondrial creatine kinase, insulin-like growth factor-binding protein 4, and adipocyte fatty acid-binding protein 4. The changes of the proteins from baseline to Week 52 were generally concordant with the changes from the baseline to Week 12, except empagliflozin reduced levels of kidney injury molecule-1 by ≥10% at Week 52, but not at Week 12. The most common biological action of differentially expressed proteins appeared to be the promotion of autophagic flux in the heart, kidney or endothelium, a feature of 6 proteins. Other effects of differentially expressed proteins on the heart included the reduction of oxidative stress, inhibition of inflammation and fibrosis, and the enhancement of mitochondrial health and energy, repair, and regenerative capacity. The actions of differentially expressed proteins in the kidney involved promotion of autophagy, integrity and regeneration, suppression of renal inflammation and fibrosis, and modulation of renal tubular sodium reabsorption. Conclusions: Changes in circulating protein levels in patients with heart failure are consistent with the findings of experimental studies that have shown that the effects of SGLT2 inhibitors are likely related to actions on the heart and kidney to promote autophagic flux, nutrient deprivation signalling and transmembrane sodium transport. Structured Graphical Abstract: Structured Graphical Abstract Favourable biological and cellular actions of differentially expressed proteins in the heart and kidney. IGFBP1, insulin-like growth factor-binding protein 1; TfR1, transferrin receptor protein 1; EPO, erythropoietin; TGM2, protein-glutamine gamma-glutamyltransferase 2; TMSB10, thymosin beta-10; uMtCK, mitochondrial creatine kinase U-type; IGFBP4, insulin-like growth factor-binding protein 4; EpCAM, epithelial cell adhesion molecule; PLA2, phospholipase A2; ANGPTL4, angiopoietin-related protein 4; RBP2, retinol-binding protein 2; CCN5, CCN family member 5; FST, follistatin; Mdk, midkine; GUCA, guanylin.